BLOCKCHAIN-BASED COVID-19 TEST CERTIFICATE STORAGE - Budiono, Rakhmad
In early 2020, the world health organization declared that the world is facing the COVID-19 pandemic. This pandemic is caused by the emergence of a new type of coronavirus which spreads very quickly. Because of this pandemic, the government has issued health protocols that use a lot of COVID-19 tests. However, cases of forgery of test certificates often occur in paper-based test certificate. To overcome this problem, a COVID-19 test certificate storage system was created using blockchain technology. By using blockchain technology, the system can be used by multiple entities, even though the entities that use it do not trust each other. This is possible because blockchain is a technology that uses a decentralized network that can store its data with a secure consensus mechanism. The system built using the Ethereum platform which is a public non-permissioned blockchain that supports decentralized application development through smart contracts that executed via EVM (Ethereum Virtual Machine). On the Ethereum platform, the system has developed using 3-layers architecture, which contains network, software, and application layer. The system successfully fulfills the COVID-19 test certificate storage requirement. The system can be used for tester registration, and create, revoke, display certificates. Also, by using encryption and digital signature mechanism, the system can protect patient privacy and data integrity. The system has also succeeded in fulfilling the availability and security requirement but failed to fulfill performance requirement. The system provides an average response time of 33 seconds, which is more than the reasonable time defined by the requirement of 30 seconds.